Does Sports Industry Matter in Human Wellbeing: Evidence From China? - Wang, De Ping; Lin, Juan (Frontiers in Public Health, 2022)
It is widely considered that sport and physical activities contribute to the development of human well-being. It is a fact that sport brings positive energy, discipline, and human wellbeing. Sports have an enormous effect on human health. Therefore, we assess the effects of the sports industry on the human health of China by using the autoregressive distributed lag (ARDL) approach from 1998 to 2020. Findings show that sports activities significantly improve human health and wellbeing. Tourism has found a positive influence on health and helped to contribute to human wellbeing. Empirical results prove that health expenditure and financial development significantly increase the population health in China. China's government should focus on the sports and tourism industry to play an important role in human health and wellbeing.